2022
DOI: 10.1155/2022/7742035
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Nomogram-Based Prediction Model for Clinical Prognosis of Patients with Stage II and III Colon Cancer Who Underwent Xelox Chemotherapy after Laparoscopic Radical Resection

Abstract: Objective. To construct a nomogram-based prediction model for the clinical prognosis of patients with stage II and III colon cancer who underwent Xelox chemotherapy after laparoscopic radical resection based on large data sets. Methods. A total of 7,832 patients with colorectal cancer who received postoperative Xelox-based chemotherapy were screened from the Surveillance, Epidemiology, and End Results database (USA) as the training data set. In addition, 348 domestic patients were screened as the validation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They concluded that age < 65, tumor size ≤ 5 cm, AJCC stage II, radiotherapy, and chemotherapy were associated with better CSS in colorectal SRCC patients (Zhao et al 2020 ). Studies have shown that tumor TNM stage was closely related to colorectal tumor prognosis (Mlecnik et al 2023 ; Sun et al 2022 ; Delattre et al 2022 ). A total of 714 (67.5%) patients with the T3 stage, 259 (24.5%) patients with the N0 stage, 249 (23.6%) patients with the N1 stage, and 547 (51.8%) patients with the N2 stage were enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that age < 65, tumor size ≤ 5 cm, AJCC stage II, radiotherapy, and chemotherapy were associated with better CSS in colorectal SRCC patients (Zhao et al 2020 ). Studies have shown that tumor TNM stage was closely related to colorectal tumor prognosis (Mlecnik et al 2023 ; Sun et al 2022 ; Delattre et al 2022 ). A total of 714 (67.5%) patients with the T3 stage, 259 (24.5%) patients with the N0 stage, 249 (23.6%) patients with the N1 stage, and 547 (51.8%) patients with the N2 stage were enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%